TANGGUNG JAWAB ORANG TUA TERHADAP ANAK DALAM PENDIDIKAN SEKSUAL (Studi Analisis Pemikiran Abdullah Nashih Ulwan) - Umami, Linda; Julaihah, Elis Siti; Rahmanwangsih, Yuli Altri (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This study analyzes the discussion of Abdullah Nashih Ulwan found in the Tarbiyatul Aulad book which focuses on the discussion of parental responsibility for children in sexual education. This study yields the following conclusions: According to Abdullah Nashih Ulwan important sexual education gets special attention from parents, so parents know ways to educate and direct children and can be responsible as educators perfectly for the people who are their responsibility. Islamic teachings do not exclude any aspect of all aspects of education including aspects of sexual education. Sexual education for children according to Abdullah Nashih Ulwan includes: 1) avoiding children from sexual stimuli, 2) explaining sexual problems to children openly.